How many meals should you skip before undergoing a colonoscopy? A randomized controlled trial: association between duration of abstinence from solid food to cleanliness of the bowel in patients undergoing elective colonoscopy - Aziz, DAA; Peow, LH; Zakaria, J; Nor, MM; Latiff, ZA (Dove Medical Press Ltd, 2024)
Indexed by WOS